2009
DOI: 10.1161/circinterventions.108.778647
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Angiography Versus Intravascular Ultrasound-Directed Bare-Metal Coronary Stent Placement (The AVID Trial)

Abstract: for the AVID InvestigatorsBackground-AVID (Angiography Versus Intravascular ultrasound-Directed stent placement) is a multicenter, randomized controlled trial designed to assess the effect of intravascular ultrasound (IVUS)-directed stent placement on the 12-month rate of target lesion revascularization (TLR). Methods and Results-After elective coronary stent placement and an optimal angiographic result (Ͻ10% stenosis), 800 patients were randomized to Angiography-or IVUS-directed therapy. Blinded IVUS was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 16 publications
2
77
0
3
Order By: Relevance
“…Primary endpoint: Major adverse cardiac events Seven articles [5][6][7][8][9]18,19 (n = 2.186) evaluated MACE ( Figure 2). IVUS stenting was associated with a nonsignificant reduction of 21% in MACE compared to ANGIO stenting (RR: 0.79; 95% CI: 0.61-1.03; I 2 : 44%).…”
Section: Effects Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary endpoint: Major adverse cardiac events Seven articles [5][6][7][8][9]18,19 (n = 2.186) evaluated MACE ( Figure 2). IVUS stenting was associated with a nonsignificant reduction of 21% in MACE compared to ANGIO stenting (RR: 0.79; 95% CI: 0.61-1.03; I 2 : 44%).…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…Analyzing individual outcomes, we observed that IVUS stenting was associated with a non-significant increase of 35% in all-cause mortality [5][6][7][8][9][18][19][20] Figure 2). Based on the GRADE approach, the overall quality of evidence was moderate for all-cause mortality (on basis of the imprecision of the results) and low for myocardial infarction (based on imprecision and the inconsistency of the results) ( Table 3).…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…However, IVUS-guided PCI could not always achieve perfect stent optimization even in noncomplex lesions. In the AVID trial 14) the number of patients that met a minimal stent area above 90% of the reference vessel was only 44%. Approximately 80% of the study population's minimum stent area was above 80% of the average of the proximal and distal reference lumen area in RESIST.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT) represent two techniques that provide essential information on preprocedural lesion characteristics (i.e., lesion severity, landing zone, and plaque composition) and the result after stent implantation (i.e., stent expansion and eccentricity, strut apposition, lesion coverage, tissue protrusion, and dissections). A total of 11 randomized controlled trials investigated the effect of IVUS-guided PCI with mixed results (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Of note, studies including patients with an increased complexity [i.e., chronic total occlusion (CTO) or lesion length >28 mm] demonstrated a consistent benefit of IVUS-guided PCI as compared with angiography, mainly driven by a reduction of repeat revascularization for restenosis (MACE at 1 year: CTO-IVUS, 2.6% vs. 7.1%, P=0.035; IVUS-XPL, 2.9% vs. 5.8%, P=0.007) (1,2).…”
Section: What Was Known Before Ilumienmentioning
confidence: 99%